2011
DOI: 10.1177/0098628311411781
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Psychological Health Concerns

Abstract: The current study explored whether an affliction similar to Medical Student Syndrome occurs in psychology students (i.e., Psychology Student Syndrome) by examining the relationship between self ratings of psychological health and the number of psychopathology courses taken. Undergraduate participants rated their level of concern about suffering from symptoms of psychological disorders. Students additionally completed a Big Five measure to determine whether personality plays a role in self diagnosis. No evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It was also common to warn students against practicing their burgeoning diagnostic skills in real life. Fear of causing medical student syndrome is a likely cause of such warnings, but it is worth noting that the effects of medical student syndrome appear to be overstated (Deo & Lymburner, 2011; Hardy & Calhoun, 1997). Thus, the more important point to stress may be that taking one course does not provide the expertise needed to make true clinical judgments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also common to warn students against practicing their burgeoning diagnostic skills in real life. Fear of causing medical student syndrome is a likely cause of such warnings, but it is worth noting that the effects of medical student syndrome appear to be overstated (Deo & Lymburner, 2011; Hardy & Calhoun, 1997). Thus, the more important point to stress may be that taking one course does not provide the expertise needed to make true clinical judgments.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, instructors do not wish to stigmatize mental illness and, thus, warn students to avoid showing disrespect for individuals with mental health problems (Gilewksi, 2011). Although some students bring real mental health problems to the classroom, Abnormal Psychology instructors are also concerned with medical student syndrome, which occurs when students erroneously worry that they have the illnesses that they are learning about in class (Deo & Lymburner, 2011; Hardy & Calhoun, 1997). To prevent this phenomenon, instructors warn students not to diagnose themselves, family, or friends.…”
mentioning
confidence: 99%
“…Medical student disease is also known as noso-phobia meaning fear of disease 11 . It gained its attention in mid 1960s after the researchers reported that 70% students complained of various mental illnesses, they had during their psychiatry rotation 12 .…”
Section: Medical Student Syndrome: a Hypochondriacal Distress In Undergraduates-verity Or Mythmentioning
confidence: 99%